Rapid Detection of Ampicillin Resistance in Escherichia coli by Quantitative Mass Spectrometry - Grundt, A. (American Society for Microbiology, 2012)
Early targeted antimicrobial therapy helps decrease costs and prevents the spread of antimicrobial resistance, including in Escherichia coli, the most frequent Gram-negative bacterium that causes sepsis. Therefore, rapid susceptibility testing represents the major prerequisite for knowledge-based successful antimicrobial treatment. To accelerate testing for antibiotic susceptibility, we have developed a new mass spectrometry-based assay for antibiotic susceptibility testing (MAAST). For proof of principle, we present an ampicillin susceptibility test for E. coli with a turnaround time of 90 min upon growth detection.